2020
DOI: 10.1021/acsaem.0c01484
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Band Engineering via MI3 (M = Sb, Bi) Doping Remarkably Enhances the Air Stability of Perovskite CsSnI3

Abstract: CsSnI 3 is a representative all-inorganic and less toxic perovskite material. However, extreme structural and chemical instability of perovskite CsSnI 3 makes its optoelectronic applications highly challenging. Upon exposure to air and moisture, it immediately undergoes a phase transition to a thermodynamically more stable, but optoelectronically inactive, one-dimensional polymorph near ambient temperature and ultimately deforms into Cs 2 SnI 6 . To prohibit this undesirable process, perovskite CsSnI 3 has to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…As the air exposure time was prolonged, the intensity of new peaks corresponding to the (111), (002), (222), and (004) lattice planes of Cs 2 SnI 6 increased. [ 27–29,31 ] A peak corresponding to the (011) lattice plane of CsI was also observed, confirming the decomposition and oxidation mechanisms as reported previously. [ 27,28,32–35 ] It was reported that there are two chemical reactions involved: CsSnI 3 → CsI + SnI 2 and 2CsI + 2SnI 2 + O 2 → Cs 2 SnI 6 + SnO 2 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As the air exposure time was prolonged, the intensity of new peaks corresponding to the (111), (002), (222), and (004) lattice planes of Cs 2 SnI 6 increased. [ 27–29,31 ] A peak corresponding to the (011) lattice plane of CsI was also observed, confirming the decomposition and oxidation mechanisms as reported previously. [ 27,28,32–35 ] It was reported that there are two chemical reactions involved: CsSnI 3 → CsI + SnI 2 and 2CsI + 2SnI 2 + O 2 → Cs 2 SnI 6 + SnO 2 .…”
Section: Resultssupporting
confidence: 89%
“…After 24 h, the absorption spectrum was almost the same with a hump around 680 nm, which can be attributed to the presence of Cs 2 SnI 6 . [ 27–29 ] In addition, the presence of Cs 2 SnI 6 was confirmed from the XRD patterns shown in Figure 2c. As the air exposure time was prolonged, the intensity of new peaks corresponding to the (111), (002), (222), and (004) lattice planes of Cs 2 SnI 6 increased.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In 2016, Jellicoe et al first synthesized CsSnI 3 PQDs via a hot-injection method. [128] However, the as-synthesized CsSnI 3 [124] Copyright 2020, American Chemical Society.…”
Section: Low-dimensional Cssni 3 Perovskitesmentioning
confidence: 99%
“…Figure 9. a) Local atoms structure of MI 3 (M ¼ Sb, Bi) doped B-γ and Y phase CsSnI 3 perovskite based on the DFT results; Calculated electronic band structure and projected density of state (PDOS) of b) SbI 3 -doped and c) BiI 3 -doped B-γ CsSnI 3 perovskite. Reproduced with permission [124]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%